The Financial State of Local Communities: A Comparative Research of Ukraine and the Czech Republic - Kozlov, Dmytro; Derev’yanko, Yuriy; Piven, Vladyslav; Melnyk, Leonid; Kubatko, Oleksandr (Economics and Business, 2021)
The article describes the specific details of local communities functioning in Ukraine and the Czech Republic. It has been examined that Ukraine and the Czech Republic have similar, but not identical systems of local governance. We conducted a comparative analysis of the financial state of local communities in both countries by five indicators. Indicator 1 (total income per capita) characterises the community’s financial potential and reveals that Ukraine’s local communities have fewer financial resources to use. Indicator 2 (total expenditures per capita) describes the ability to provide residents with the resources generated in their community and Czech communities have a higher value of this indicator. Indicator 3 (share of the administrative expenditures) shows the effectiveness of money spent, and local communities in both Ukraine and the Czech Republic spend particularly the same part of their total expenditures on administrative needs. Indicator 4 (capital expenditures per capita) demonstrate how the money generated is spent on urgent capital investments and Ukraine’s communities have much lower capital expenditures per capita than Czech ones. Indicator 5 (the share of capital expenditures in total expenditures) reflects how local communities perceive the importance of investments in capital projects and Ukraine’s communities spend fewer financial resources for capital needs than Czech ones.